The girls who disappeared eaudiobook A novel. - Douglas, Claire (HarperAudio, 2023)
"Claire Douglas is a mistress at weaving the reader into a web of domestic deceit."—Jane Corry, author of The Dead Ex A journalist's life is threatened when she investigates the truth about a mysterious car crash that happened twenty years earlier in this gripping thriller from the internationally bestselling author of The Couple at Number 9 and Just Like the Other Girls. A car accident. Three missing girls. A twenty-year mystery. A woman on the verge of discovering the truth . . . In a rural Wilshire town lies the Devil's Corridor—a haunted road which has witnessed eerie happenings, from unexplained deaths to the sounds of a child crying in the night. In this bucolic stretch of Southwest England famous for its otherworldly sites, nothing is more puzzling than the Olivia Rutherford case. Four girls were driving home. After their car crashed only one—Olivia—was found. What happened to the girls who disappeared? On the twentieth anniversary of the tragedy, journalist Jenna Halliday has arrived in Wiltshire to cover the case. The locals aren't happy with this outsider determined to dig into the past. Least of all Olivia. Soon, Jenna starts receiving menacing notes. The locals have made it clear she's not welcome. But someone is going to make her leave one way or another. Jenna's been warned: she must get out of this town before she suffers a dark fate . . . and becomes another mystery attached to this place.